Banana pseudostem sap: A waste plant resource for making thermally stable cellulosic substrate. (November 2016) - Basak, S; Saxena, S; Chattopadhyay, SK; Narkar, R; Mahangade, R
The flame retardant functionality was imparted in cellulosic textile using banana pseudostem sap, an eco-friendly waste plant product. The extracted sap was applied in three different pH conditions, viz. acidic, neutral and alkaline to the pre-mordanted bleached and mercerized cotton fabrics. Flame retardant characteristics of both the control and the treated fabrics were analysed in terms of limiting oxygen index, vertical flammability and heat release related properties using a cone calorimeter. The thermal degradation and pyrolysis mechanism were studied using thermogravimetric analysis and differential scanning calorimetry. The elemental analysis was carried out with X-ray fluorescence, and the quantification of phosphorus and nitrogen was also done. Besides, the charring mechanism of both the control and the treated fabric was analysed in detail, and a char structure model has been proposed. The treated fabrics were also evaluated in terms of colour and other physical properties.